Training and Development in Institutions of Higher Education in Lao P.D.R - Phimmasenh, Khanthaly (Universiti Malaysia Sarawak (UNIMAS), 2017)
This study examined training and development program from seven dimensions; strengths of training program, weaknesses and benefits of training programs for university lecturers and for higher learning institutions. The study also examined training activities organized by institution to support training and development, various components involved in training program and suitable training model for a higher learning institution. This research was conducted qualitatively to get in-depth understanding of the training programs. Purposive sampling method was used where informants were chosen based on their job tittle and the university they belong to. There were twelve informants interviewed, coming from various universities and from diverse field of studies. Data for this study were collected through open-ended survey, structured interview and documentary analysis. Data were analyzed using content analysis approach. There are many identified benefits of training program in higher learning institutions as well as several new findings have also been discovered in this study. Finding from the study revealed that training program helped to increase capability of university lecturers, improved job performance and also organizational performance. Through this research, the practitioners are able to develop the appropriate training model in the context of higher educational institution and work together towards improving the practice.